Кинетика твердофазных реакций и ионно-электронная проводимость а оксидных системах - Зинченко, В.Ф.; Садковская, Л.В.; Менчук, Е.М. (Вісник Українського матеріалознавчого товариства, 2013)
The general phenomenological principles of kinetics of solid-phase reactions with oxide layer formation are considered. Special cases of the kinetic equations are established under various limiting conditions and mechanisms of reactions. The interrelation between the rate of solidphase reactions in oxides systems and a parity of ionic and electronic components of their conductivity is established. It is shown that an optimum condition for course of solid-phase reactions is the approximate parity of ionic and electronic a component. The general principles of experimental determination of components of conductivity in oxide systems are described. The method of application of high-temperature conductometry for determination of kinetic parameters of solidphase reactions and degree of stabilisation of valence states of elements in complex oxides systems is offered.